(untitled) (مجلة الرازي الطبية, 2025)
β-thalassemia major is the most common chronic hemolytic anemia in Iraq, treated with multiple transfusions. The present study was carried out to evaluate Serum testosterone in male patients and estradiol in female patients with β-Thalassemia major and the effects of frequent blood transfusions. In this study, eighty patients were employed and categorized into two groups: 51 males (63.7%) with age range 14–30years and 29 females (36.3%) with an age range 13–30 years, while 40 normal healthy individuals were chosen as a control group, 23 male (57.5%) and 17 female (42.5%) for comparison. ELISA was used to measure the levels of testosterone and estradiol in the serum. The mean levels of serum testosterone (1.64 ± 1.75) and estradiol (14.77 ± 12.30) were significantly lower in β-thalassaemia patients than in controls (p < 0.001). In patients with hypogonadism, the mean age for the start of blood transfusion was significantly lower compared to those with eugonadism, with a P value of 0.003. There was a significant decrease in height percentile in hypogonadism thalassemic patients compared to eugonadism patients (p value = 0.01). In contrast to healthy controls, the study shows that patients with β-thalassemia major have significantly lower serum levels of testosterone and estradiol, suggesting that hypogonadism is quite prevalent in this population.